1995
DOI: 10.1007/bf02209009
|View full text |Cite
|
Sign up to set email alerts
|

Detection and partial sequence analysis ofHelicobacter pylori DNA in the bile samples

Abstract: The existence of Helicobacter pylori in the biliary tract was investigated. Seven bile samples were included in this study. Among them, six bile samples were collected by percutaneous transhepatic cholangiodrainage and the other by needle aspiration during cholecystectomy. Using nested PCR with two sets of primers homologous to the urease A gene, Helicobacter pylori DNA was detected. Three samples, one from a patient with advanced gastric cancer involving the pancreatic head and two from patients with pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Although Helicobacter pylori is recognized as a human pathogen associated with gastric lesions, recent studies have revealed convincingly the presence of several Helicobacter species in the hepatobiliary system. [7][8][9][10][11][12][13][14][15][16][17][18] A microorganism resembling H. pylori was firstly detected in resected gallbladder (GB) mucosa of patient with gallstone by Kawaguchi et al in 1996 7 and bile-resistant hepatic Helicobacter species such as H. bilis, H. pullorum, and F. rappini were extracted from GB mucosa and bile juice of patients with chronic cholecystitis, suggesting that these agents may be key elements in the development of various GB-related diseases, especially GB cancer. 9 The pres-ence of H. pylori DNA in gallstones was established by PCR in several reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Helicobacter pylori is recognized as a human pathogen associated with gastric lesions, recent studies have revealed convincingly the presence of several Helicobacter species in the hepatobiliary system. [7][8][9][10][11][12][13][14][15][16][17][18] A microorganism resembling H. pylori was firstly detected in resected gallbladder (GB) mucosa of patient with gallstone by Kawaguchi et al in 1996 7 and bile-resistant hepatic Helicobacter species such as H. bilis, H. pullorum, and F. rappini were extracted from GB mucosa and bile juice of patients with chronic cholecystitis, suggesting that these agents may be key elements in the development of various GB-related diseases, especially GB cancer. 9 The pres-ence of H. pylori DNA in gallstones was established by PCR in several reports.…”
Section: Introductionmentioning
confidence: 99%
“…9 The pres-ence of H. pylori DNA in gallstones was established by PCR in several reports. [12][13][14] Together with the discovery of H. pylori in bile juice, [16][17][18] this has led to the suggestion that Helicobacter species are etiological agents in gallstone formation. However, another study from Germany reported no association of Helicobacter species with gallstone formation suggesting possible ethical and regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…Whether H. pylori participates in the pathogenesis of biliary diseases is a question that has been addressed by several investigators. The DNA of H. pylori has been identified in the bile, liver, and biliary epithelium of patients with hepatobiliary diseases [1,2,3]. In regard to the biliary diseases, in one study, H. pylori specific ureB DNA was detected in the gallbladder tissue of a Japanese patient with gallstone and cholecystitis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Chen et al [5] found H. pylori ureA and ureB DNA in 13.55% of the gallbladders of patients with cholecystitis. However, in a study evaluating the presence of H. pylori ureA DNA in the bile by nested PCR, Lin et al [1] observed a negative result in four patients with biliary diseases. Queiroz et al [6] were able to isolate H. pylori strain from the liver of a Brazilian patient with cirrhosis, which indicates that H. pylori may be viable in the human liver.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge led to investigations into a potential relationship between Helicobacter species and hepatobiliary diseases. The relationship between H. pylori and liver diseases has been assessed in humans, and several reports have demonstrated the prevalence of H. pylori in hepatobiliary diseases [20][21][22]. Previous study reported that H. pylori or related similar H. pylori could be detected in liver tissues from patients with cholestatic liver diseases [21].…”
Section: Discussionmentioning
confidence: 99%